1989
DOI: 10.1161/01.hyp.13.6.658
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium and control of vascular function. State of the Art lecture.

Abstract: The response of isolated blood vessels to a variety of vasoactive agonists is modulated by the presence of endothelial cells. Indeed, these cells can release both dilator and constrictor substances. The major endothelium-derived relaxing factor may be nitric oxide, which activates soluble guanylate cyclase in the smooth muscle, although the endothelial cells also secrete an unidentified hyperpolarizing factor. Among the natural stimuli for the release of endotheliumderived relaxing factors are circulating horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
328
0
18

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(353 citation statements)
references
References 66 publications
7
328
0
18
Order By: Relevance
“…Acetylcholine (ACh) causes significant relaxation of the arteries (Fujii et aI., 1992;Furchgott and Zawadzki, 1980;Vanhoutte, 1989), although the role of ACh in brain during decreases in blood pressure is still under dis cussion. Recently, cholinergic deficits in the brain are considered to have a close relationship with im pairments of cognitive function (Moran et aI., 1994; Perry et aI., 1977; Wilcock et aI., 1982), and the Abbreviations used: ACh, acetylcholine; AChEI, acetylcho linesterase inhibitor; ANOY A, analysis of variance; EDRF, en dothelium-derived relaxing factor; MAP, mean arterial pressure; SHR, spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine (ACh) causes significant relaxation of the arteries (Fujii et aI., 1992;Furchgott and Zawadzki, 1980;Vanhoutte, 1989), although the role of ACh in brain during decreases in blood pressure is still under dis cussion. Recently, cholinergic deficits in the brain are considered to have a close relationship with im pairments of cognitive function (Moran et aI., 1994; Perry et aI., 1977; Wilcock et aI., 1982), and the Abbreviations used: ACh, acetylcholine; AChEI, acetylcho linesterase inhibitor; ANOY A, analysis of variance; EDRF, en dothelium-derived relaxing factor; MAP, mean arterial pressure; SHR, spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, it is well known that the endothelium secretes various vasoactive agents, such as the vasodilators NO, prostacyclin and endothelium-derived hyperpolarizing factor and the vasoconstrictors, such as endothelin-1, angiotensin II (Ang II) and thromboxane A 2 . [22][23][24][25] It is concluded that the endothelium is the biggest endocrine organ in the human body. A healthy endothelium maintains vascular tone and structure by regulating the balance between vasodilation and vasoconstriction, growth inhibition and growth promotion, antithrombosis and prothrombosis, anti-inflammation and proinflammation, and also antioxidation and pro-oxidation.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…A healthy endothelium maintains vascular tone and structure by regulating the balance between vasodilation and vasoconstriction, growth inhibition and growth promotion, antithrombosis and prothrombosis, anti-inflammation and proinflammation, and also antioxidation and pro-oxidation. [23][24][25][26] The simple molecule NO regulates basal vascular tone, at least in part, by about 50% in the brachial artery in humans. 11,26 Thus, loss of healthy endothelial function becomes a trigger of atherosclerosis.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Impaired flow-mediated dilatation (FMD) in the brachial artery is characterised by loss of endothelium-dependent vascular smooth muscle relaxation in response to vasodilator stimuli (1). The resultant effect of this impairment may be partly due to alterations in the nitric oxide (NO) pathway, notably a reduction in endotheliumderived NO bioavailability (2)(3).…”
Section: Introductionmentioning
confidence: 99%